Low Dielectric Behavior of a Robust, Guest‐Free Magnesium(II)–Organic Framework: A Potential Application of an Alkaline‐Earth Metal Compound. Issue 10 (18th March 2015) - Mendiratta, Shruti; Usman, Muhammad; Tseng, Tien‐Wen; Luo, Tzuoo‐Tsair; Lee, Shang‐Fan; Zhao, Li; Wu, Maw‐Kuen; Lee, Mandy M.; Sun, Shih‐Sheng; Lin, Ying‐Chih; Lu, Kuang‐Lieh
Abstract: A robust and low dielectric 3D metal–organic framework [Mg(phen)(bdc)] n (1 ; phen = 1, 10‐phenanthroline, bdc 2– = 1, 4‐benzenedicarboxylate) was hydrothermally synthesized from magnesium acetate, H2 bdc, and phen ligands. Compound1 has a non‐interpenetrated network with an uncommon cds‐type topology. Chemical and dielectric investigations of this material indicate that it retains a high chemical stability and has a low dielectric constant of 3.33 ± 0.1 (at 100 kHz), which is the lowest value for Mg‐based MOFs reported to date. In addition, temperature‐dependent dielectric studies revealed that its low dielectric constant is retained over a wider temperature range. Mg‐based MOFs have the advantage of being a new class of dielectric materials because of their many intrinsic properties. Abstract : A 3D, robust, and low dielectric (low‐ κ ) Mg‐based MOF with a non‐interpenetrated cds‐type topology was prepared. Dielectric measurements revealed the κ value to be 3.33 ± 0.1 (at 100 kHz). It is evident that the incorporation of alkaline‐earth metal ions in highly porous frameworks could result in materials with low‐ κ properties.